Analisis Kesalahan Siswa Kelas VIII Dalam Menyelesaikan Soal Cerita Pada Materi Teorema Pythagoras di SMP Muhammadiyah 5 Surakarta Tahun Ajaran 2016/2017 - Sulistyawan, Moch Anang; , Drs. Ariyanto, M.Pd (2017)
This research was conducted with the aim of describing the error and to know the factors causing the students to make mistakes in solving the story on the material Pythagorean Theorem. This type of research is qualitative descriptive. Subjects of this study were 30 students of class VIII A in SMP Muhammadiyah Surakarta 5. Data collection techniques in this study using the test method, observation, and interviews. Data validation was done by triangulation method, by comparing the test results with the interview. Data analysis techniques carried out in three stages: data reduction, data presentation, and data verification and conclusion. The analytical framework developed by the category mistake Newman. There four types of errors are errors of understanding, transformation error, error process skills, and mistakes conclusion answers. The causes of these errors in general is due to the ability of students can not interpret the matter, as well as the level of understanding and creativity of students low in identifying the real problems into mathematical models.